THE INFLUENCE OF GENUINE REVENUE, GENERAL ALLOCATION FUNDS, SPECIAL ALLOCATION FUNDS AND OIL AND GAS PRODUCT SHARING FUNDS ON THE ECONOMIC GROWTH OF ACEH PROVINCE - Iskandar; Nanda Safarida; Khairatun Hisan; Putri Sarah Farucha (RADJA PUBLIKA, 2023)
This study aims to analyze the effect of regional own-source revenue, general allocation funds, special allocation funds, and oil and gas profit-sharing funds on the economic growth of Aceh province using the Vector Auto Regression (VAR)/ Vector Error Correction Model (VECM) method. The results showed that based on the VECM estimation test, in the short term, local revenue and general allocation funds had a negative and significant effect on economic growth. Meanwhile, the special allocation fund variable has a positive and insignificant long term effect. however, the oil and gas profit-sharing fund variable has a negative and significant effect on the economic growth of Aceh province. In general, based on the IRF test, the shock that occurred in the variables of general allocation funds and oil and gas profit-sharing funds was responded negatively by economic growth.